2018
DOI: 10.1016/j.jrras.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic evaluation of safety parameters and neutron flux spectra in the MNSR research reactor using DRAGON-4 code

Abstract: Comparative studies for conversion of the fuel from high enriched uranium (HEU) to low enriched uranium (LEU) in the reactor (MNSR) were performed using DRAGON code deterministic. In this work the HEU fuel (UAl 4-Al, 90% enriched with Al-clad) and LEU (12.6% UO 2 enriched with zircaloy-4 alloy clad) cores were analyzed. This model was utilized in this work to calculate the neutron energy flux spectrum in the first inner and outer irradiation sites of the Miniature Neutron Source Reactor (MNSR). The continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…The predicted spectra exhibit a distribution pattern typical for thermal reactors, and consist of a thermal Maxwellian, followed by a flat epithermal neutron spectrum and a fission-like fast neutron component 46 . It is also similar to spectra reported for other thermal neutron beamlines, such as the Neutron Radiography Reactor (NRAD) at the Idaho National Laboratory (INL) in USA 47 , Thermal and Epi-thermal Neutron Irradiation Station (TENIS) at the Institut Laue-Langevin in France 48 , Syrian Miniature Neutron Source Reactor (MNSR) 49 , or Kalpakkam Mini reactor (KAIMINI) in India 50 . However, Giegel, et al 47 reported that the epithermal and fast neutron components are approximately 2 and 10 times higher than the thermal component.…”
Section: Discussionsupporting
confidence: 75%
“…The predicted spectra exhibit a distribution pattern typical for thermal reactors, and consist of a thermal Maxwellian, followed by a flat epithermal neutron spectrum and a fission-like fast neutron component 46 . It is also similar to spectra reported for other thermal neutron beamlines, such as the Neutron Radiography Reactor (NRAD) at the Idaho National Laboratory (INL) in USA 47 , Thermal and Epi-thermal Neutron Irradiation Station (TENIS) at the Institut Laue-Langevin in France 48 , Syrian Miniature Neutron Source Reactor (MNSR) 49 , or Kalpakkam Mini reactor (KAIMINI) in India 50 . However, Giegel, et al 47 reported that the epithermal and fast neutron components are approximately 2 and 10 times higher than the thermal component.…”
Section: Discussionsupporting
confidence: 75%
“…The predicted spectra exhibit a distribution pattern typical for thermal reactors, and consist of a thermal Maxwellian, followed by a flat epithermal neutron spectrum and a fission-like fast neutron component 55 . It is also similar to spectra reported for other thermal neutron beamlines, such as the Neutron Radiography Reactor (NRAD) at the Idaho National Laboratory (INL) in USA 56 , Thermal and Epi-thermal Neutron Irradiation Station (TENIS) at the Institut Laue-Langevin in France 57 , Syrian Miniature Neutron Source Reactor (MNSR) 58 , or Kalpakkam Mini reactor (KAIMINI) in India 59 . Giegel et al 56 reported that the epithermal and fast neutron components are approximately 2 and 10 times higher than the thermal component.…”
Section: Discussionsupporting
confidence: 75%
“…The spectrum energy of neutron can be classified into three regions, namely thermal (0<E<0.625 eV), intermediate (0.625 eV<E<0.5 MeV), and fast (E>0.5MeV). Fast neutrons are produced from fission reaction, whereas thermal and intermediate neutrons are results of neutron interaction with reactor materials, in form of slowing down process [9].…”
Section: Theory Neutron Sources In Reactormentioning
confidence: 99%